Harnessing models and big data to enable climate-resilient agriculture in India: Kick-off workshop - Foster, Timothy; Kramer, Berber; Kannan, Samyuktha (International Food Policy Research Institute, 2019)
Risk is considered one of the main barriers to investments in agriculture. The Picture-based Insurance (PBI) project in India, funded by 3ie, evaluates the impact of an innovative insurance scheme. Such impact evaluations are important in improving products/services, making informed policy decisions regarding investments that can generate welfare and economic development, and advancing the scientific literature.